Examination of the influence of stimuli eccentricity on the inhibitory control in a simon task within virtual reality - Dan Bürger; Luisa Peintner; Florian Heilmann; Stefan Pastel; Kerstin Witte (PLoS ONE, 2025)
In certain scenarios, suppressing automated responses and initiating alternative actions is necessary to respond appropriately to stimuli. This process, known as inhibitory control, can be investigated using the Simon task, where stimuli positions are typically task-irrelevant but affect reaction times when stimulus location and response direction differ (Simon effect). Given the importance of reacting to peripheral stimuli in sports and everyday life, this study aimed to examine the influence of stimulus eccentricity on the Simon effect. To this end, a virtual reality version of the Simon task was developed, in which red and green stimuli appeared at different eccentricities (22°, 45°, and 60°), eliciting hand movements to the left or right. Virtual reality allowed for precise control of experimental conditions and simultaneous data collection. Reaction times to congruent (matching stimulus location and response direction) and incongruent (mismatched) stimuli were compared across eccentricities. The results showed significantly larger Simon effects (reaction time differences between incongruent and congruent trials) with increasing stimulus eccentricity, with a greater increase in reaction times for incongruent conditions compared to congruent conditions. As the Simon effect stems from the discrepancy between stimulus location and response direction, it appears to intensify as this discrepancy increases. The study’s limitations include the difficulty of perceiving color stimuli in the visual periphery and its primary laboratory setting, suggesting future research to use geometric shapes instead of colors and incorporate complex virtual reality scenarios to improve the ecological validity of the findings.